THE RELATIONSHIP OF WORK STRESS TO THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL INSPECTORATE OF SIKKA DISTRICT - Maria Julistiya K. Sewar; Luh Putu Ruliati; Cathrin W. D. Geghi; Marylin Susanti (PROFESSIONAL HEALTH JOURNAL, 2025)
Performance is a measure of individual or group success in carrying out tasks and responsibilities, as well as the ability to achieve predetermined goals and standards. Of all the regions in NTT province, Kupang City took the top spot with the highest percentage of reporting, at 95.27%. Southwest Sumba Regency ranked second with a reporting achievement of 69.83%, and followed by the NTT Provincial government which ranked third with a reporting percentage of 66.38%. This study aims to determine the relationship of job stress to employee performance at the Regional Inspectorate of Sikka Regency. The type of research used is analytic observational using Cross Sectional design. The sample in this study were 31 respondents. Samples in this study were taken with simple random sampling technique. The data analysis used was univariate analysis and bivariate analysis, using the Chi-square statistical test. The results of this study indicate that the variables associated with employee performance are workload (p = 0.047), working hours (p = 0.017), work pressure (p = 0.042) and work motivation (p = 0.020). This study highlights the importance of effective human resource management in improving the performance of an agency or organization.